Nursing care for women with anxiety and depression during pregnancy: an integrative review (Research, Society and Development, 2020)
Objective: To demonstrate the importance of knowledge about anxiety and depression during pregnancy for improving the quality of prenatal care in Basic Health Care. Methodology: This is an integrative review of the literature carried out with articles published and indexed in the Virtual Health Library (VHL) and the LILACS and MEDLINE databases. Results and discussion: Of the 34 articles found, after applying inclusion and exclusion criteria and analyzing their contents, 09 were selected for the study analysis. Characteristics that stood out in the occurrence of problems to harmonize the psychological during and after the gravidic period were identified. Conclusion: Anxiety and depression are present, mainly in adolescent mothers, mothers with low schooling, without family support, and single mothers, thus the influence of socioeconomic factors as risk factors for these disorders in pregnancy. As a strategy for quality care to pregnant women with depression and anxiety, the Psychological Prenatal allied with multiprofessional follow-up has proved essential.